Degarelix as a neoadjuvant hormonal therapy for acute urinary tract toxicity associated with external beam radiotherapy for intermediate- and high-risk prostate cancer: a propensity score matched analysis. (2nd September 2020) - Hata, Shinro; Shin, Toshitaka; Abe, Satoki; Kawano, Kaori; Sato, Ryuta; Kai, Tomoki; Shibuya, Tadamasa; Ando, Tadasuke; Mimata, Hiromitsu
Abstract: Background: In prostate cancer treatment, lower urinary tract symptoms significantly improve with luteinizing hormone-releasing hormone antagonists use compared with agonists. However, it is unclear whether luteinizing hormone-releasing hormone antagonists can decrease acute urinary tract toxicity during external beam radiotherapy. This study aimed to assess whether luteinizing hormone-releasing hormone antagonists used as neoadjuvant therapy reduced acute urinary tract toxicity during external beam radiotherapy compared with luteinizing hormone-releasing hormone agonists. Methods: The study included 78 patients who underwent intensity-modulated radiation therapy for intermediate- and high-risk prostate cancer between April 2013 and January 2020. Irradiation was initiated after 3–6 months of neoadjuvant therapy. Androgen deprivation therapy was given to the intermediate-risk group for 6 months and the high-risk group for 2–3 years. The European Organization for Research and Treatment of Cancer/Radiation Therapy Oncology Group toxicity grading scale was used to evaluate the urinary tract system toxicity. Relevant clinical factors were used in matching patients based on propensity scores to enable comparison between the groups. Results: Each group had 27 matched patients. There was no reduction in urinary tract toxicity with the use of luteinizing hormone-releasing hormon antagonists ( P  = 0.624). For patients with an International Prostate Symptom Score of ≥11 at the start of treatment, 18 patients in each group were matched. Significantly lower scores were observed in the luteinizing hormone-releasing hormon antagonist group ( P  = 0.041). Conclusions: Luteinizing hormone-releasing hormon antagonists may reduce acute urinary tract toxicity during prostate cancer external beam radiotherapy compared with luteinizing hormone-releasing hormon agonists, in particular in patients with moderate to severe symptoms at the start of treatment. Abstract : It is unclear whether luteinizing hormone-releasing hormone antagonists can decrease acute urinary tract toxicity during prostate cancer external beam radiotherapy. We found that degarelix reduces acute urinary tract toxicity during radiotherapy.